Cherokee Marsh: a Case Study in Residential Perceptions of Nutrient Runoff in the Yahara River Watershed - Perttunen, Eric; Patton, Liam; Roth, Leo (My University, 2016)
The Cherokee Marsh in Madison, Wisconsin, wrestles with eutrophication issues due to constant influxes of phosphorus from urban and agricultural sources. A lack of vegetative buffers, soils with poor phosphorus storage potential, and nearby impervious surfaces all facilitate transport of nutrients into Cherokee Marsh. Legislators passed the Wisconsin Zero Phosphorus Fertilizer Law in 2010 in an attempt to minimize urban phosphorus fluxes. Our research seeks to understand whether significant differences in lawn care behaviors and knowledge of environmental regulations exist between two neighborhoods, one close to and one far from Cherokee Marsh. We consulted USDA soil maps and conducted a survey in those two neighborhoods. Our soil map of the Cherokee Marsh area suggests that the soils bordering the marsh retain phosphorus poorly, pointing to the criticality of phosphorus reduction efforts around marshes. Our survey indicates similar lawn care behaviors and awareness of environmental regulation in the two neighborhoods. The marsh-adjacent neighborhood demonstrated slightly higher concern for fertilizer’s impacts on the marsh. We recommend additional research to solidify understanding of the relationship between neighborhood proximity to a natural area and residents’ awareness of the socio-environmental issues facing that natural area, and how to accordingly address those particular issues.
Includes Maps, Aerial photos, Figures, Graphs, Photographs, Tables, Appendices and Bibliography.
Keywords: Cherokee Marsh; Nutrient runoff; Yahara River Watershed; Residential perceptions; Eutrophication; Phosphorus